Evaluation of Vietnam’s Current Legal Provisions on State Land Acquisition: Amending the Law to Combat Corruption and Promote Socioeconomic Development (Passagens: Revista Internacional de História Política e Cultura Jurídica, 2022)
This article is developed from evaluation of provisions of Vietnam’s 2013 Land Law on State land acquisition for socioeconomic development in the national or public interest. Since implementation, many legal loopholes have been revealed, such as large-scale land acquisition, “cheap” compensation for acquired property, and coercive land acquisitions. These have created additional opportunities for corrupt officials and enterprises who have a close and mutually profitable relationship, putting the people whose land is to be acquired into difficulties and poverty. Amending the law to close these loopholes is especially necessary to combat corruption, ensure the interests of people whose land is to be acquired, and promote Vietnam’s socioeconomic development.